Traffic Congestion Assessment Based on Speed Index Performance on Arterial Streets in the Commercial Center of Latakia - اسعد شذى (Latakia University Journal -Engineering Sciences Series, 2021)
The high traffic density causes traffic congestion on the road, causing delays before it reaches its destination, in addition to the stress and high psychological impact on the driver, it also results in staff and staff being late for work and students being late for school, With frequent accidents on these busy roads. Congestion has a lot of reasons, one of them is poor infrastructure that leads to a state of congestion, a significant increase in the number of vehicles, a lack of prior information for road users about the traffic situation, Division of traffic management into several departments (Public works, municipality, security, transport…). They become ineffective in some areas, aggressive driving style Which may be an effective factor in creating congestion, in addition to the use of individual transport rather than mass transport. Latakia suffers from a very poor transport system, and the indiscriminate movement of vehicles on its streets. This has been accompanied by increased traffic, which has led to many problems. The most important is the problem of congestion, in terms of increasing the values of delay times in different road sectors. This has contributed to major traffic crises and congestion. It affected service levels on arterial streets in the city’s downtown, in the absence of rush-hour studies. Two main streets have been selected in the commercial and downtown center of Latakia City, which is an important arterial street for the distribution of movement. These arterial streets connect the commercial and administrative center of the city with the other parties of the city. The moving controller analyses a large number of actual speeds of the vehicle, measured in each sector, with a view to estimating congestion, calculating its indicators, and determining peak hours. Congestion levels were inferred based on the values of the speed performance index, and the average speeds of daytime and evening peak hours have been mapped to considered street sectors.